Beginning Drupal 7 - Tomlinson, Todd. (New York, N.Y. Apress Distributed to the book trade worldwide by Springer-Verlag New York, 2010)
Presents information on creating and managing a Web site with Drupal 7, covering such topics as content options, taxonomy, menus, installing themes, blocks, modules, views, panels, and administration.
Keywords: Drupal (Computer file).; Web site development; Web sites -- Design; Open source software